2015
DOI: 10.4067/s0718-27242015000300001
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship and Academic Employment-More Alike than You'd Think

Abstract: Abstract:Recognising the increasing value of knowledge and technology transfer, the scientific and political communities in Germany have recently devoted much attention to academic entrepreneurship. Seeking to explore similarities and differences between academic employment and entrepreneurship, we interviewed 112 postdoctoral students from the four major German research organisations and 16 senior transfer managers whose responsibilities included spin-off facilitation.Our findings indicate that those involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
1
15
0
1
Order By: Relevance
“…Besides that, complementary business/administration education affected the creation of new spin-offs negatively. Additionally, a study by Sinell et al (2015) indicated that typical postdoctoral students considered business sector as a risky activity that implied a significant career change for them. Hence, this study seeks to identify the causes and reasons for this contradictory role of high levels of founder's education on their entrepreneurial motivations.…”
Section: Exploring the Role Of Education On The Entrepreneurial Motivmentioning
confidence: 99%
“…Besides that, complementary business/administration education affected the creation of new spin-offs negatively. Additionally, a study by Sinell et al (2015) indicated that typical postdoctoral students considered business sector as a risky activity that implied a significant career change for them. Hence, this study seeks to identify the causes and reasons for this contradictory role of high levels of founder's education on their entrepreneurial motivations.…”
Section: Exploring the Role Of Education On The Entrepreneurial Motivmentioning
confidence: 99%
“…Academics might experience particular difficulty in overcoming the challenges of entrepreneurship because they often regard industry as a completely alien environment and because they lack business-related resources and skills (Franklin et al, 2001; Rasmussen & Wright, 2015;Sinell et al, 2015). Even when they do successfully initiate spin-offs, they rarely invite non-scientific specialists to join (Ensley & Hmieleski, 2005; Franklin et al, 2001; Knockaert et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing its benefits, European decision makers in academia, industry, and government increasingly regard academic entrepreneurship as the third "academic mission" and continue to introduce wide-ranging support initiatives. Nonetheless, transfer performance in Europe still lags behind that of universities in the United States (Audretsch & Göktepe-Hultén, 2015).Academics might experience particular difficulty in overcoming the challenges of entrepreneurship because they often regard industry as a completely alien environment and because they lack business-related resources and skills (Franklin et al, 2001; Rasmussen & Wright, 2015;Sinell et al, 2015). Even when they do successfully initiate spin-offs, they rarely invite non-scientific specialists to join (Ensley & Hmieleski, 2005; Franklin et al, 2001; Knockaert et al, 2011).…”
mentioning
confidence: 99%
“…Masculine hegemony is challenged when there are female partners in the venture capital firms, making it 50% more likely that startups with female members will receive investment (Brush et al, 2014). In the case of founding an academic spin-off, the perception prevails that entrepreneurship and academia systematically differ in their work logics (Sinell et al, 2015;van der Sijde et al, 2014): entrepreneurship is seen to have little appeal to scientists who are also uncertain about how to cross over into the business sphere.…”
Section: Gender-specific Constraints On Academic Entrepreneurship Andmentioning
confidence: 99%